E-Learning Platforms as Leverage for Education for Sustainable Development - Donath, Liliana; Mircea, Gabriela; Rozman, Tomislav (European Journal of Sustainable Development, 2020)
The paper is a conceptual approach to education for sustainable development using an e-learning platform. It starts from the observed reality that all education stakeholders need a learning environment where they can have access to knowledge, collaborate and share their experience, as a survey conducted among students and companies in Timisoara, Romania, region shows. The proposed multi-stakeholder environment accommodates two sections: the learning environment mostly dedicated to students, trainees, tutors and mentors and the virtual sustainability centre that is dedicated to on-line meetings, workshops, counselling, etc. Durable learning is supported by a range of written digital and multimedia resources, including pre-recorded on-line tutoring, videos and games. To engage online learners, various gamification techniques were used in the course design phase, such as recording and presenting the learner’s progress, role-playing and similar. The article presents a conceptual design of the learner’s journey and a mapping from gamification concepts to Moodle LMS elements. Keywords: E-learning, education, sustainable development, gamification, LMS